Comparison of the Effect of Quiet Eye Training and Anticipation Training on the Performance of Hockey Goalkeepers - Masoumeh Aliasghari-Toyeh; Farhad Ghadiri; Saeed Arsham; Rasoul Yaali (Vesnu Publications, 2018)
Introduction: Cognitive-perceptual skills are important for successful performance in many tasks. The aim of this study was to compare the effects of quiet eye training and anticipation training on performance of hockey goalkeepers. Materials and Methods: In this semi-experimental study, 10 hockey goalkeepers were selected via purposeful sampling method, and randomly assigned to two equal groups of quiet eye training and anticipation training. The study included pretest, intervention, posttest, and transference stages. Participants in pretest, posttest, and transfer (under-pressure position) stages received 25 hockey strokes at a distance of 9 meters. Intervention was done for three consecutive days (9 blocks of 40 trials, a total of 360 trials), and participants received their training instructions. Data were analyzed using independent t and dependent t tests via SPSS software. Results: Both anticipation training (P = 0.010) and quiet eye training (P < 0.001) had significant effect on the performance of hockey goalkeepers. Moreover, quiet eye training group had better performance compared to anticipation training group in both normal (P = 0.010) and under-pressure (P = 0.010) conditions. Conclusion: Quiet eye training in contrast to anticipation training results in better performance in normal and under-pressure conditions.